Guest editorial: Open educational resources in engineering education: Various perspectives opening the education of engineers - Piedra Pullaguari, N. (2014)
Open Educational Resources (OER) provide a strategic opportunity to improve the quality of education as well as facilitate policy dialog, knowledge sharing, and capacity building. One of the fundamental concepts of OER is 'the ability to freely adapt and reuse existing pieces of knowledge.' Reuse of educational resources by both individuals and organizations may have significant creative and economic benefit for the educational environment. This Special Issue editorial introduces six interesting experiences, representative of the use of OER in engineering education in important areas such as the production of open content at various scales, reuse of contents, institutional open Web site initiatives, and technological applications to support the exploitation of OER, all at different degrees of maturity. Since some readers will be unfamiliar with prior work on OER, this Special Issue also outlines the hot topics in OER and the critical factors for success when joining the Open Educational Movement. Finally, the editorial provides a set of recommendations and examples offered by the Special Issue editors from their over 6 years of experience leading a research group in semantic Web technologies applied to Open Education. A key requirement, in their opinion, is to improve the metadata interoperability between various collections of open material, so as to facilitate the discoverability and subsequent combining, remixing, or adapting OER; that is, OER data should be easily accessible to any user.